How Do Islamic Job Satisfaction, Organizational Commitment, and Islamic Work Ethic Influence Intention to Leave in Islamic-Based Companies? - Mini Arni; Muhammad Irfani Hendri; Arman Jaya; Nurul Komari; Mazayatul Mufrihah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Employee retention remains a critical challenge for Islamic-based organizations, where value congruence and ethical climate strongly influence employee attitudes. Drawing on Social Exchange Theory, this study aims to examine the effect of Islamic Job Satisfaction on Intention to Leave, with Organizational Commitment as a mediator and Islamic Work Ethic as a moderator. A quantitative explanatory survey was conducted among 165 employees in Islamic-based organizations in Indonesia, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLSc) in SmartPLS 4. The results indicate that Islamic Job Satisfaction significantly reduces Intention to Leave both directly and indirectly through Organizational Commitment. Organizational Commitment also shows a strong negative effect on Intention to Leave. Furthermore, Islamic Work Ethic moderates the relationships between Islamic Job Satisfaction and Organizational Commitment and between Organizational Commitment and Intention to Leave by weakening these effects. These findings highlight the crucial role of spiritual and ethical values as internal regulatory mechanisms that strengthen employee retention and provide important managerial implications for sustaining workforce stability in Islamic-based organizations.